Anorectal functions after perineal and retropubic radical prostatectomy - a prospective clinical and anal manometric assessment - GİRAL, ADNAN (TERMEDIA PUBLISHING HOUSE LTD, 2011)
Introduction: The aim of this study is to evaluate the anorectal functions of prostate cancer patients who have undergone radical perinea! prostatectomy (RPP) or radical retropubic prostatectomy (RRP) surgery. Material and methods: Thirty-seven patients with an indication for radical prostatectomy were included after informed consent. Anorectal manometry was performed before and one month after the surgery in 22 RPP and 15 RRP patients in our clinic. Clinical assessment was evaluated by anorectal functions with anal incontinence scoring (AIS) (Fernandez; no incontinence = 0; maximal incontinence = 12). Patients with a history of anorectal surgery were excluded from the study. The following data were recorded: external anal sphincteric pressure (EASP), internal anal sphincteric pressure (IASP), minimum ano-rectal reflex volume (MARRV) and minimum rectal sensory volume (MRSV). Results: In the RPP and RRP groups, the mean age was 66 (56-75) and 64.3 (52-73) years, respectively. In the RPP group, EASP and IASP values showed a significant decrease after the surgery. In the RRP group, EASP and IASP were also decreased after the surgery, but without statistical significance. No significant change was seen in MARRV and MRSV of either group. When the scores of AIS were analysed, no significant clinical difference between pre- or post-operative scores was seen in RPP and RRP groups. Conclusions: Perineal or retropubic surgery may injure pelvic floor muscles and/or supplying nerves, which likely causes anorectal dysfunction. Although there is a significant decrease in early postoperative EASP and IASP after RPP, it has no clinical significance according to AIS.
Keywords: anal incontinence; perineum; prostate; prostatic neoplasms; FECAL INCONTINENCE